2000
DOI: 10.1562/0031-8655(2000)0720681taoaah2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of 5-Aminolevulinic Acid Hexyl Ester and 5-Aminolevulinic Acid to Normal Nude Mouse Skin: Differences in Protoporphyrin IX Fluorescence Kinetics and the Role of the Stratum Corneum¶

Abstract: An important limitation of topical 5‐aminolevulinic acid (ALA)‐based photodetection and photodynamic therapy is that the amount of the fluorescing and photosensitizing product protoporphyrin IX (PpIX) formed is limited. The reason for this is probably the limited diffusion of ALA through the stratum corneum. A solution to this problem might be found in the use of ALA derivatives, as these compounds are more lipophilic and therefore might have better penetration properties than ALA itself. Previous studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…It has already been demonstrated (van den Akker et al, 2000) that after topical application of He-ALA, the stratum corneum of the skin acts as a barrier impairing its penetration through the skin. It has also been observed that topical use of He-ALA restricts porphyrin accumulation to the site of application (Casas et al, 2001b;Moan et al, 2001), but the same intensity of PpIX fluorescence using lower concentrations of ALA esters compared to ALA was obtained in the tissue layers of normal rat colon (Endlicher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been demonstrated (van den Akker et al, 2000) that after topical application of He-ALA, the stratum corneum of the skin acts as a barrier impairing its penetration through the skin. It has also been observed that topical use of He-ALA restricts porphyrin accumulation to the site of application (Casas et al, 2001b;Moan et al, 2001), but the same intensity of PpIX fluorescence using lower concentrations of ALA esters compared to ALA was obtained in the tissue layers of normal rat colon (Endlicher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…i.v. or topical formulations, could be further developed to allow rapid and even distribution of photosensitizer across the tumor by using specific penetrant enhancers ( 25 ). In addition, modification of the delivery vehicle gel‐1 to enhance normal tissue clearance of PME could be further investigated for application in PDD.…”
Section: Discussionmentioning
confidence: 99%
“…The formulation is generally left in place for 4–6 h before a biopsy is taken from the application site. Sectioning of the biopsy allows the fluorescence intensity of PpIX to be evaluated using suitable microscopy with excitation wavelengths around 400 nm and emission wavelengths from 600 to 700 nm (3,65). Alternatively, PpIX is extracted from dissolved tissue samples and determined using fluorescence spectrophotometry with similar excitation and emission wavelengths as above (33,66,67).…”
Section: Tissue Disposition Of Ala Following Topical Administrationmentioning
confidence: 99%
“…Their purpose is to remove the stratum corneum and keratinized debris overlying lesions and, thereby, enhance drug penetration (43,60,62,136,137). In a semiquantitative study, Van den Akker et al (65) demonstrated reduced PpIX production due to the reservoir capacity of the stratum comeum after topical application of hexyl ALA. When the stratum comeum was removed by tape stripping, PpIX production equalized between topically applied hexyl ALA and ALA. De Rosa et al (91) quantified the amounts of topically applied ALA or ALA esters retained in the stratum comeum in vitro .…”
Section: Tissue Penetration Enhancement Strategiesmentioning
confidence: 99%